Elaboración de una bebida energética a partir de mucílago de cacao (Theobroma Cacao L.) saborizada con café (Coffea) - López Narváez, Sindy Paola (2022)
Energy drinks are products that among their main characteristics is to help improve the physiological performance of the human body, this project wants to provide new alternatives in the market for energy drinks in the Province of Los Ríos, with the objective of elaboration an energy drink from cocoa mucilage (Theobroma cacao L.) of the varieties CCN51 and Nacional using different concentrations of coffee (Coffea). A factorial design A*B was applied, the factors studied are A (Varieties of cocoa) and B (Formulations) which correspond to 6 treatments with 3 replicates, obtaining a total of 12 experimental units, for the statistical treatment of the data it was used the INFOSTAT software and to know the statistical differences, Tukey's significance test was applied at 5%. The operations in the production of energy drink from cocoa mucilage are: reception, washing, cutting, pulping/pressing, pasteurized1, formulation, dilution, pasteurized2 packaging/sealed and stored, for the acceptability of the drink a survey was carried out on 20 panelists who determined that treatment 5 has the best formulation (20% mucilage of the National variety with 1% coffee), presenting better characteristics of flavor, aroma and color. The physicochemical parameters evaluated were: pH, acidity, °Bx, density, ashes, moisture, protein, carbohydrates, energy and alkaloids (at the best treatment). Keywords: energy drink, elaboration, mucilage, varieties